Rebooting “Failed” Family-Based Treatment - Lavender, Kellie R. (Frontiers in Psychiatry, 2020)
Family Based Treatment (FBT) has become well established as the first-line evidence-based treatment for adolescents with anorexia nervosa. However, fidelity to the FBT model can be poor, and treatment is often augmented or modified in various untested forms in the hope of increasing its effectiveness and acceptability. The New Zealand Eating Disorders Clinic, a private specialist outpatient clinic in New Zealand, has been seeing increasing numbers of families presenting for treatment reporting an experience of “failed FBT.” All of the families who presented with a child under the age nineteen living at home agreed to restart FBT with the author when re-engaging in treatment. This essay summarizes the experience of the author in repeating FBT with previously “failed” FBT cases over 20 months between 2017 and 2019. Common themes of the first course of FBT were identified that raised questions for the author as to whether FBT had been implemented with sufficient fidelity and proficiency the first time around. This clinical perspective essay describes how these identified issues were addressed when FBT was administered again. It does not intend to make broad claims, but instead is intended to be helpful to clinicians who are implementing FBT, to assist them in carefully examining and assessing whether key FBT principles and procedures have been exhausted before evaluating the need for modification or augmentation. Furthermore, this perspective provides suggestions as to how the identified common themes can be addressed if families re-present for FBT treatment after having had a course of “failed FBT”.